Model Matematika Penyakti Diabetes Melitus - muh irwan; Irwan Irwan; jusrawati jusrawati (Jurnal Varian, 2019)
Diabetes mellitus (DM) or often known as diabetes mellitus, is a disease that can be caused by heredity, one of the factors caused by patterns of human life patterns. In the paper a model and mathematical analysis of DM disease are introduced. To simplify the analysis, the Runge Kutta method was used to complete the model. Based on the results of the analysis, it is known that the population of patients with DM disease tends to increase for a long period of time.